Evaluation and verification of requirements artifacts: A Checklist applied to User Stories and Prototype - Martins, Thiago S.; Araújo, Lucas S.; Oran, Ana Carolina (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2025: Anais do XXIV Simpósio Brasileiro de Qualidade de Software, 2025)
The quality of system requirements is essential to ensure that the software meets user needs. In the context of software engineering, specifying requirements through user stories and prototypes has become a widely adopted practice in the industry, as it facilitates effective communication among requirements, development, and testing teams. However, for these practices to be effective, information essential to developing functionality must be clearly specified and organized. To support this verification process and ensure the completeness of artifacts, this work proposes VUSP (Checklist for the Assessment and Verification of User Stories and Prototypes), focused on the verification of requirements artifacts. The feasibility of VUSP was evaluated in a study involving 38 participants from a Software Engineering course at the Federal University of Amazonas, who used the checklist to verify user stories and prototypes. Participants provided feedback on the tool’s usability and effectiveness using the TAM (Technology Acceptance Model), addressing aspects such as perceived ease of use, work relevance, and behavioral intention. The results indicate that VUSP helped identify improvements in documentation and the centralization of essential information for development.